2021
DOI: 10.1080/21655979.2021.1940616
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol suppresses malignant progression of oral squamous cell carcinoma cells by inducing the ZNF750/RAC1 signaling pathway

Abstract: This study examined whether activation of zinc finger protein 750/Ras-related C3 botulinum toxin substrate 1 (ZNF750/RAC1) signaling pathway may be involved in the ability of resveratrol to inhibit malignant progression of CAL-27 oral squamous cell carcinoma cells. CAL-27 cells were treated with resveratrol and transfected with plasmids expressing a ZNF750 mimic or ZNF750 inhibitor. Cell proliferation and apoptosis were assessed. Western blotting was used to examine the effects of resveratrol on levels of angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…VEGF and MMP-2 are involved in the invasion of malignant cells to surrounding healthy tissue [ 30 , 31 ]. Besides, VEGF is implicated in regulating angiogenesis [ 32 , 33 ] and plays an important role in the metastasis of OSCC [ 34 , 35 ]. In view of this, the decreased invasion and angiogenesis by EVO mediated by RAGE could be related to the alteration of expression levels of VEGF and MMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF and MMP-2 are involved in the invasion of malignant cells to surrounding healthy tissue [ 30 , 31 ]. Besides, VEGF is implicated in regulating angiogenesis [ 32 , 33 ] and plays an important role in the metastasis of OSCC [ 34 , 35 ]. In view of this, the decreased invasion and angiogenesis by EVO mediated by RAGE could be related to the alteration of expression levels of VEGF and MMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that treated mice exhibited significant inhibition of cancer cell metastasis [73]. In addition, Xiao et al demonstrated that RES can inhibit the malignant progression of CAL-27 oral squamous cell carcinoma cells by down-regulating the expression of vascular endothelial growth factor (VEGF), RGS5, CD105, and cell adhesion molecules ITGA5, ITGB1, and CD44 via the zinc finger protein 750/Ras-related C3 botulinum toxin substrate 1 (ZNF750/RAC1) signaling pathway, leading to a reduction in vascular normalization, metastasis, adhesion, and migration of CAL-27 cells [74]. Similarly, Chang et al reported that RES can suppress the metastatic behavior of cisplatin-resistant human oral cancer cells by inhibiting the ERK/p-38 signaling pathway and MMP-2/9.…”
Section: In Vitro Studies Of Resveratrol On Anticancer Activitymentioning
confidence: 99%
“…Resveratrol inhibits the expression of the target gene MUC5AC by inhibiting the expression of gene SPDEF in lung mucinous adenocarcinoma cells (Lin et al, 2021). Resveratrol inhibits malignant progression of CAL‐27 oral squamous cell carcinoma to some extent (Xiao et al, 2021).…”
Section: Biological Activitiesmentioning
confidence: 99%